The impact of economic crisis on the balance of payment of Pakistan - Yaseen, Muzamal (2023)
This study examines the impact of the economic crisis on the balance of payments in Pakistan, an emerging nation in South Asia facing various economic challenges. The research question focuses on understanding the consequences of the crisis on the country's balance of payments, which is a key indicator of its international trade and investment flows. An empirical analysis is conducted using macroeconomic variables such as economic growth, exchange rates, and the current account balance. The study employs tests including lag length determination, Johansen cointegration test, Granger causality test, and Variance Decomposition Analysis. The findings reveal a long-term relationship between the examined variables, indicating the existence of cointegration. The study also identifies the number of vectors and investigates the causal relationships between the variables. Furthermore, the Variance Decomposition Analysis sheds light on the factors influencing changes in the model's series. The research provides valuable insights into the state of Pakistan's economy and offers recommendations for policymakers to improve the balance of payments and restore economic stability.